METHODOLOGY EVALUATION OF PIN MICRORELIEF METER - Melo,Mariana C. (2017)
ABSTRACT: The effects of natural weathering and different managements performed in agriculture may best be understood by studying the soil roughness. The aim of this study was to evaluate the optimization of the use of pin microrelief meter, an instrument used to determine the soil surface roughness, as the number of readings collected over traditional methodology proposed in the bibliography. The study was conducted in Rio Paranaiba (MG), in a Haplustox soil. The experimental design was completely randomized in a 2×3 factorial design with four replications. There were combined two types of primary tillage: conventional tillage with disc plow (PCAD) and harrow (PCGA), and three amounts of readings (100, 200, and 300 reading points) sampled in each experimental unit. Independently of the soil tillage, disc plow and harrow, the collection of 100 readings using a pin microrelief meter of a square meter, was sufficient to determine the surface roughness before and after soil preparation, without accuracy loss compared with the traditional method.